(untitled) (Islamic Sciences Journal, 2026)
This research deals with project financing through margin. This research aims to review the concept of margin, the types of investment in it, the advantages of investing through margin, the risks of investing through it, and then consider its legal ruling on this financing, the conditions that must be available in the contract, and the legal controls